How do value proposition and brand orientation influence business survival in the presence of government support? - Nor Hafiza, Othman; Nurul Faizah, Halim; Hasif Rafidee, Hasbollah; Nurul Ashykin, Abd Aziz (Czestochowa University of Technology, 2024)
During crises, businesses often struggle with performance challenges, where a well-defined value proposition and brand orientation are crucial for survival. Despite the importance, research on how these factors impact franchisee survival, especially with government support as a moderating factor, remains scarce. This study addresses this gap by examining how government support interacts with value proposition and brand orientation to affect franchisee survival in Malaysia. Data were collected through a survey of 246 homegrown franchisee owners across multiple sectors using purposive sampling and were analyzed with IBM SPSS 26 and SmartPLS 4.0 software. The results indicate that a robust value proposition significantly enhances franchisee survival, with government support amplifying this effect. These findings underscore the critical role of a clear value proposition in ensuring franchisee continuity during crises and provide valuable insights for policymakers and government agencies to devise effective strategies for business sustainability.